Kudus Regency Archives and Library Department’ Roles in Building Disabilities Social Capital Through Computer Classes - Amelia, Bella Septi; Prasetyawan, Yanuar Yoga (Syarif Hidayatullah State Islamic University of Jakarta, 2024)
This research was motivated by the inequality in access for people with disabilities in using computers. This disparity was caused by several factors, including the limitations faced by individuals, economic factors, capacity in mastering technology, availability of suitable technology, and low social support for people with disabilities. The purpose of this study was to determine the role of the library as social capital in the computer class program for people with disabilities at the Archives and Library Department of Kudus Regency. The research method used in this study was a qualitative method with a case study approach. Data collection was carried out through semi-structured interviews and document studies. The informants in this study consisted of ten people selected through purposive sampling. These ten informants included librarians and disabled individuals participating in the computer class program. The data analysis technique used was thematic analysis, which involved analyzing interview transcripts, coding the main meanings, and identifying themes based on the similarities of the codes. The results of this study showed that the computer class program at the Archive and Library Department Kudus Regency provided many benefits to people with disabilities. The library became a place where cooperation was formed between people with disabilities and various parties, leading to the birth of a social network, which is a key element of social capital. The social capital that developed played a crucial role in helping people with disabilities overcome various social problems. With the support of social networks, mutual trust, and cooperation, people with disabilities could more easily access the resources, opportunities, and services they needed. Secondly, social capital helped people with disabilities acquire basic computer skills, which opened up opportunities for them to become more independent and actively participate in the digital world. Additionally, social capital helped people with disabilities prepare for jobs and contributed to changing their fate.